A manual of nuclear medicine procedures - Das, Birendra K.; Noreen Norfaraheen Lee Abdullah (Penerbit Universiti Sains Malaysia, 2012)
This manual is designed primarily to be of assistance to trainee nuclear medicine technicians and radiographers. It will also be of value to those who are already trained in the safe handling and use of radionuclides for imaging, as a rapid reference for routine and non-routine nuclear medicine imaging procedures. The procedures described were largely developed or modified at the Nuclear Medicine Department, Guy's Hospital, London, with regular updates during the last 10 years